Educational Administration in the Shadow of Technology: A Heideggerian Analysis of School Governance Digitalization - Sri Mulyani, Ucu Agustini; Setiawati; Adu, Ifedayo Emmanuel (Universitas Islam Negeri Raden Intan Lampung, 2025)
The digital transformation of educational administration has become a central phenomenon in Indonesian schools, characterized by the adoption of e-reporting systems, e-staffing, digital attendance, and e-budgeting. This article critically analyzes the impact of educational administration digitalization from a Heideggerian perspective, focusing on the concepts of Gestell and Enframing. Research conducted in two secondary schools in Sukabumi reveals that while digitalization enhances efficiency, transparency, and data integration, it also leads to consequences such as increased workloads, technostress, digital surveillance, and the erosion of social spaces and care practices within the school environment. Philosophical analysis shows that digital technology is not merely a tool but reshapes human existence and relationships in education, potentially leading to dehumanization and alienation. However, adaptive strategies and spaces of resistance have emerged through digital learning communities and informal collaboration. This article highlights the importance of a human-centered approach in educational administration digitalization policies and practices, ensuring that digital transformation serves as a tool for empowerment and humanization, rather than control and efficiency.